Increased infiltration of M2-macrophages, T-cells and PD-L1 expression in high grade leiomyosarcomas supports immunotherapeutic strategies. (1st February 2018) - Kostine, Marie; Briaire-de Bruijn, Inge H.; Cleven, Arjen H. G.; Vervat, Carly; Corver, Willem E.; Schilham, Marco W.; Van Beelen, Els; van Boven, Hester; Haas, Rick L.; Italiano, Antoine; Cleton-Jansen, Anne-Marie; Bovée, Judith V. M. G.
ABSTRACT: Background: Immunotherapy may be a rational strategy in leiomyosarcoma (LMS), a tumor known for its genomic complexity. As a prerequisite for therapeutic applications, we characterized the immune microenvironment in LMS, as well as its prognostic value. Methods: CD163 + macrophages, CD3 + T-cells, PD-L1/PD-L2 and HLA class I expression (HCA2, HC10 and β2m) were evaluated using immunohistochemistry in primary tumors (n = 75), local relapses (n = 6) and metastases (n = 19) of 87 LMS patients, as well as in benign leiomyomas (n = 7). Correlation with clinicopathological parameters and survival analyses were assessed. Effect of LMS cells on macrophage differentiation was investigated using coculture of CD14 + monocytes with LMS cell lines or their conditioned media (CM). Results: 58% and 52% of the tumors were highly infiltrated with CD163 + macrophages and T-cells, respectively, with HLA class I expression observed in almost all tumors and PD-L1 expression in 30%. PD-L2 expression was also detected in some PD-L1 + tumors. All these immune markers correlated with high tumor grade but only CD163 associated with overall survival ( p = 0.003) and disease-specific survival ( p = 0.041). In vitro, CD163 was upregulated in the presence of LMS cells producing M-CSF, suggesting that this tumor drives macrophages towards the M2 phenotype. Conclusion: The clinical significance of M2 macrophages, possibly induced by LMS cell-secreted factors, suggests that 2/3 of high-grade LMS patients might benefit from macrophage-targeting agents. Furthermore, PD-L1 expression together with high T-cell infiltrate and HLA class I expression in around 30% of high grade LMS reflects an active immune microenvironment potentially responsive to immune checkpoint inhibitors.